EQUIPMENT RENTAL PARTY TOOLS PROGRAM APPLICATION SYSTEM WITH VISUAL BASIC on PAMILI BROTHER - Sigit Sumanto; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2004)
In this study, the authors try to present information with a computerized rental, so it can assist officers in carrying out transactions a day - day. Data - data that is on the computer, among other renters data, transaction data, price lists, payment receipts and transaction reports daily - days. Because in the present moment many people need tents and rental services for data recording was manually by an officer so that data is less accurate and efficient. Therefore, the author offers one the best solution is to use a computer so that data is more accurate and efficient. With the existence of computer tools, we can see information about the type or size of biodata tenants who rented tents and tents yag still there. The data also needs to be backed up to storage media better to avoid it - it is not desired. And this computer system should be used by employees who already have skills in computer systems to achieve good work, hence the need for good working conditions among the people - people involved in the computerized system, both directly and indirectly.